Indicator Accuracy and Monetary Policy: Is Ignorance Bliss? - Kristoffer P. Nimark (Sveriges Riksbank, 2003)
This paper argues that assuming a common information set shared by the public and the central bank may be inappropriate when one is concerned with the value of information itself. Specifically, we argue that it may lead one to draw the conclusion that monetary policy do not benefit from accurate real time data. This paper sets up a New-Keynesian model with optimal discretionary monetary policy, where we allow for partial and diverse information. The model is used to show that monetary policy do benefit from private and accurate real time data, where private is the crucial assumption. The representative household is better of with less accurate information since this reduces the relative price distortions due to inflation and staggered prices. An implication of the negative welfare consequences of a well informed public is that central banks should be restrictive with publishing their real time data.
Keywords: E37; E47; E52; E58; 330; Monetary policy; Information; Kalman filter; Higher order beliefs; Real time data